Penyisihan Logam Cr (VI) dari Limbah Cair Elektroplating Menggunakan Mikroalga Chlorella sp. dengan Variasi Penambahan External-Glutathione - Shinta Elystia; Edward HS; Afrilia Geishy Karamy (Jurnal Serambi Engineering, 2021)
Electroplating wastewater containing metal Cr (VI), which has a high toxicity. An  alternative treatment is absorbed using microalgae Chlorella sp. Chlorella sp. has the ability to synthesize glutathione phytochelatin (GSH) to respond to the toxic effects of heavy metals. If the micro algae cannot synthesize phytochelatin properly, the cells will die due to exposure to heavy metals in a long contact time. In this study, GSH was added to the metal biosorption process by micro algae Chlorella sp. This study aimed on  determining the effect of the adding   GSH during the biosorption process. The study was conducted with variations of  GSH (0, 5, 10, and 15 mg/L) and variations of  contact time (1, 2, 3, and 4 days). The results of this study show that  high cell density occurred in the reactor with the addition of GSH 15 mg/L which is 1.72x106 cells/ml. The highest removal of Cr (VI) metal occurred in  4 day contact  with the addition of GSH 15 mg/L and obtained a 72% removal efficiency.